2022
DOI: 10.1155/2022/3710074
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of “Bushen Huoxue Therapy”-Based Combined Chinese and Western Medicine Treatment for Diabetic Kidney Disease: an Updated Meta-Analysis of 2105 Patients

Abstract: Background. Diabetic kidney disease (DKD) is the most important cause of the end-stage renal disease (ESRD) and the main cause of renal replacement therapy. Excessive inflammatory response and renal fibrosis are the keys to the development of this disease, and the conventional Western medical treatment is difficult to achieve and obtain long-term stable clinical results in all patients with DKD. Many studies have shown that Chinese medicine as a complementary and alternative medicine may be another therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[5] Several meta-analyses of the treatment of patients with CKD and CM have shown that CM has good clinical efficacy. [26,27] Due to the complex pathophysiological process of CKD-CVD, the above-mentioned treatments to control traditional risk factors have not achieved the expected efficacy in reducing CVD mortality in patients with CKD. As shown in Table 1, several clinical trials have been conducted to explore the effectiveness of CM or a combination of Chinese and Western medicines in improving the clinical outcomes of CKD or CVD patients.…”
Section: Calcium and Phosphorus Metabolism Managementmentioning
confidence: 99%
“…[5] Several meta-analyses of the treatment of patients with CKD and CM have shown that CM has good clinical efficacy. [26,27] Due to the complex pathophysiological process of CKD-CVD, the above-mentioned treatments to control traditional risk factors have not achieved the expected efficacy in reducing CVD mortality in patients with CKD. As shown in Table 1, several clinical trials have been conducted to explore the effectiveness of CM or a combination of Chinese and Western medicines in improving the clinical outcomes of CKD or CVD patients.…”
Section: Calcium and Phosphorus Metabolism Managementmentioning
confidence: 99%
“…[ 4 ] In recent years, Traditional Chinese Medicine has gained good curative effects in reducing DN symptoms, assisting in stable blood pressure reduction, glucose and lipid reduction, strengthening renal function, and delaying the progress of DN. [ 5 , 6 ] Xuebijing injection (XBJI) is a kind of traditional Chinese medicine injection, which is extracted from the effective components of traditional Chinese medicine such as Honghua, Chishao, Chuanxiong, Danshen, Danggui. It has the effects of promoting blood circulation and removing blood stasis, clearing heat and detoxification, strengthening health and tonifying deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Our previous meta-analysis based on 2105 DKD patients demonstrated that TCM combined with Western medicine significantly reduced renal damage indicators and blood glucose levels and had the same safety as conventional Western therapy. 15 Schisandra chinensis fruit Mixture (SM) is a Chinese herbal formula for DKD that consists of three herbs: Schisandra chinensis fruit ("Wuweizi" in Chinese, WWZ), Rhizoma chuanxiong ("Chuanxiong" in Chinese, CX) and Oyster shells ("Muli" in Chinese, ML). Our previous study showed that WWZ alcohol extract was effective in preventing DKD-induced EMT 16 and demonstrated that SM may treat DKD via the PI3K/AKT pathway, 17 but the exact mechanism remains to be further investigated.…”
Section: Introductionmentioning
confidence: 99%